IMPLEMENTASI DAN TANTANGAN ASEAN OPEN SKIES DALAM MENINGKATKAN KONEKTIVITAS UDARA DI ASIA TENGGARA - Aditya Nugraha, Ridha; Sungkono; Widarto, Bambang (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2025)
ASEAN Open Skies is a strategic initiative aimed at creating an open and efficient aviation market in Southeast Asia by enhancing connectivity, trade and tourism among member countries. This policy eliminates barriers to air services, both for cargo and passengers, through multilateral agreements such as the ASEAN Multilateral Agreement on the Full Liberalisation of Air Freight Services. Although this policy has great potential to improve ASEAN's competitiveness in the global market, its implementation faces various challenges, such as differences in regulations between countries, disparities in airport infrastructure, and the need to harmonize domestic policies with international standards. This study uses a normative juridical legal method with a statutory and conceptual approach to examine the challenges in implementing ASEAN Open Skies and its impact on regional air connectivity. The results show that this policy has the potential to accelerate economic growth and the tourism sector, but requires solutions to regulatory challenges and infrastructure development to achieve these goals effectively.